Analysis of Squat Training In The Sport Of Football: Systematic Literature Review - Usman, Muhammad Tahmidzi; S, Adi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the implementation of squat training in football performance analysis. This review adhered to the PRISMA guidelines for systematic reviews and meta-analyses. The studies included were published within the last five years, from January120201to July 2024. The1following keywords were used during the search process: (1) Squat; (2) Football. The Scopus research journal database was utilized for conducting the literature search. The theme of this research as a whole obtained 549. Contains 214 articles which are taken from 10 relevant articles. Conclusion: Analysis of squat training in the sport of football includes balance stability, strength, technique game tactics, advantages of integration with other exercises, increasing leg muscle strength, and improving the performance of passing kicks and shooting.